A Comparative Study of Legal Systems in the Regulation of Business Activities in Indonesia and Common Law Countries - Gunawan, Gunawan; Habeahan, Rasman; Nawas, Abu; Chotib, Muhammad; Rizki Aji Putra, Gilang (UIN Jakarta, 2025)
Economic globalization has intensified cross-border business relations, requiring a comprehensive understanding of the differences among legal systems governing business activities. Differences in legal systems, particularly between the civil law and common law systems, have a significant impact on contract formation, dispute resolution, and the protection of business actors’ interests. Indonesia, as a country that adopts the civil law system, has distinct characteristics in business regulation compared to common law countries such as the United Kingdom and the United States. This article aims to analyze the comparative legal aspects of business law between Indonesia and common law countries, with a focus on sources of law, contract law, and dispute resolution mechanisms. The research method employed is normative legal research using a comparative law approach. The findings indicate that differences in legal systems have direct implications for legal certainty, contractual flexibility, and business strategies adopted by business actors.